'The students do not know why they are here': education decision-making for Syrian refugees. (8th August 2017) - Karam, Fares J.; Monaghan, Christine; Yoder, Paul J.
ABSTRACT: This case study, conducted collaboratively between education scholars and education practitioners, describes and analyses the ways in which Syrian refugee teachers and an NGO are developing and implementing non-formal education (NFE) programming in three refugee settlements in Lebanon. Utilising the INEE Minimum Standards for Education in Emergencies, we analyse teachers' and programme administrators' decision-making processes regarding curriculum, language of instruction, and pedagogy as well as how and why these decisions are made in the absence of a guiding framework or policy for NFE. We also consider the ways in which the nation-state writ large still helps to influence these decisions in the 'global era'.